Machine learning with R : expert techniques for predictive modeling to solve all your data analysis problems - Lantz, Brett (Community experience distilled., 2015)
Perhaps you already know a bit about machine learning but have never used R, or perhaps you know a little R but are new to machine learning. In either case, this book will get you up and running quickly. It would be helpful to have a bit of familiarity with basic programming concepts, but no prior experience is required.